PROFILE OF PROCALCITONIN LEVELS IN SEVERE–CRITICAL COVID-19 PATIENTS - Asyikun Nasyid Room; Hisbullah Amin; Faisal Muchtar (Journal Medical Universitas muhammadiyah Makassar, 2021)
The diagnostic and therapeutic modalities of COVID-19 are still being researched and developed. One of the diagnostic modalities in the treatment of COVID-19, especially in patients with severe and critical symptoms, is procalcitonin. Although procalcitonin is more commonly associated with bacterial infections, several studies have shown association between the severity of COVID-19 patients and procalcitonin levels, and serial measurement of procalcitonin levels may be useful in predicting prognosis. This report presents three cases of severe-critically ill COVID-19. All three patients were tested for procalcitonin serially. Survivors (patient I and II) showed relatively low procalcitonin levels. These patients were clinically responsive to conventional oxygen therapy modalities. Serial chest X-rays in both patients also did not show the progression of pneumonia. In non-survivor (patient III) procalcitonin level have shown high value before ICU treatment, and during ICU care showed an increasing trend. The increase was in line with the progression of pneumonia on chest X-ray, and the patient is also clinically unresponsive to oxygen therapy, requiring invasive mechanical ventilation. Procalcitonin examination is one of the modalities that can be used in predicting the prognosis and disease course of severe-critical COVID-19 patients. COVID-19 patients with low procalcitonin levels are associated with a better prognosis than patients with high procalcitonin levels.